2014
DOI: 10.5812/rijm.15527
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Excessive Mobile Phone Use and its Relation With Mental Health Status and Demographic Factors Among the Students of Gonabad University of Medical Sciences in 2011 - 2012

Abstract: Background:The excessive mobile phones use is a common problem among students, so it is necessary to identify this phenomenon's relevant factors in each university for appropriate planning. Objectives: The study aim was to determine the prevalence of excessive mobile phone use and its relationship with mental health status and demographic factors on the students of Gonabad University of Medical Sciences in 2011 -2012. Patients and Methods:In this cross-sectional study, all 700 students in the university were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
40
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 15 publications
3
40
2
1
Order By: Relevance
“…Mobile phones can be used for communication everywhere and adolescent can be online at any time. Mobile phones are used by adolescents to communicate, message with each other, play games, take pictures, and connect to the Internet (Tavakolizadeh, Atarodi, Ahmadpour, & Pourgheisar, ). Along with the benefits of using mobile phones, there are concerns about their overuse (Vacaru, Shepherd, & Sheridan, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mobile phones can be used for communication everywhere and adolescent can be online at any time. Mobile phones are used by adolescents to communicate, message with each other, play games, take pictures, and connect to the Internet (Tavakolizadeh, Atarodi, Ahmadpour, & Pourgheisar, ). Along with the benefits of using mobile phones, there are concerns about their overuse (Vacaru, Shepherd, & Sheridan, ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the problematic use of mobile phones has attracted the attention of researchers and to some, is considered equivalent to drug addiction (Nikhita, Jadhav, & Ajinkya, ). Researchers have shown that the use of uncontrolled mobile phone is associated with loneliness (Tan, Pamuk, & Dönder, ), anxiety, depression (Tavakolizadeh et al, ), aggressive behaviors, insomnia, smoking, suicidality, and low self‐esteem (Yang, Yen, Ko, Cheng, & Yen, ). The present study supports these findings: the hostility subscale mean score of the adolescents who have their own mobile phones was found to be high, whereas the anxiety, depression, negative self‐esteem, somatization, and hostility mean scores were found to be high in adolescents using their mobile phones for social media.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence regarding the relationship between educational attainment and problematic cell phone usage is equivocal. While some studies point to a link between problematic cell phone usage and level of education (particularly among those undertaking extended periods of study) (Tavakolizadeh, Atarodi, Ahmadpour, Pourgheisar, 2014), others refute this (Billieux, 2012), and even report a link between low educational levels and problematic cell phone usage (Leung, 2007). Hence explanations that have been made concerning a link between problematic cell phone usage and educational attainment have not been particularly compelling.…”
Section: Demographic Factors and Smartphone Addictionmentioning
confidence: 99%
“…Mobile phone because of the ever availability and its mobility application has created a dramatic interest for youth in comparison with other communication technologies. 1 Initially, mobile phones were used only as a communication tool but these days, mobile phones function as mobile computers that serve us with music player, games, internet, video camera, calculator, alarm clock, and many more other perceived benefits as increased accessibility and social connectivity, reduced loneliness, and security in emergency situations. 2 Unfortunately, communication technology has some negative effects also.…”
mentioning
confidence: 99%